2003
DOI: 10.1128/mcb.23.17.6200-6209.2003
|View full text |Cite|
|
Sign up to set email alerts
|

Potentiation of Tumor Necrosis Factor-Induced NF-κB Activation by Deacetylase Inhibitors Is Associated with a Delayed Cytoplasmic Reappearance of IκBα

Abstract: Previous studies have implicated acetylases and deacetylases in regulating the transcriptional activity of NF-B. Here, we show that inhibitors of deacetylases such as trichostatin A (TSA) and sodium butyrate (NaBut) potentiated TNF-induced expression of several natural NF-B-driven promoters. This transcriptional synergism observed between TNF and TSA (or NaBut) required intact B sites in all promoters tested and was biologically relevant as demonstrated by RNase protection on two instances of endogenous NF-B-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
1
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 50 publications
5
71
1
2
Order By: Relevance
“…However, the underlying mechanisms seem to depend on the cell type investigated and include on the one hand an HDAC-inhibitor-mediated continual degradation of de novo synthesised IκBα protein (possibly by prolonged activation of the upstream IκB-kinase) causing prolonged presence and DNA-binding of NFκB in the nucleus and enhancing NFκB-dependent transactivation, or on the other hand a reduction in proteasomal degradation of IκBα, preventing NFκB nuclear translocation and DNA binding [4,8,[46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying mechanisms seem to depend on the cell type investigated and include on the one hand an HDAC-inhibitor-mediated continual degradation of de novo synthesised IκBα protein (possibly by prolonged activation of the upstream IκB-kinase) causing prolonged presence and DNA-binding of NFκB in the nucleus and enhancing NFκB-dependent transactivation, or on the other hand a reduction in proteasomal degradation of IκBα, preventing NFκB nuclear translocation and DNA binding [4,8,[46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…30 Enhanced proteasomal degradation of IkBa in our setting also appeared to be linked to signals upstream of its phosphorylation, because it could be counteracted by inhibition of IKKb. Correspondingly, resynthesized IkBa captured by proteasome inhibition after IL-1 þ UVB treatment displayed phosphorylation of Ser32/36 residues.…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory has previously demonstrated that histone hyperacetylation induces HIV-1 expression by specifically disrupting a single nucleosome positioned immediately downstream of the transcription start site (73)(74)(75). Moreover, HIV-1 transcription can be synergistically activated either by the viral transactivator Tat HIV-1 and HDACi through direct acetylation of Tat HIV-1 (50, 76 -78) or by NF-B and HDACi through a persistent degradation of the NF-B inhibitor I B-␣ (38,43).…”
Section: Discussionmentioning
confidence: 99%
“…In Vivo Acetylation Assays-In vivo acetylation assays were performed as described previously (43). In brief, COS-7 cells were transfected, using FuGENE-6 (Roche Molecular Biochemicals) according to the manufacturer's protocol, with expression vectors for WT-Tax BLV , Tax BLV -mut3K, HA-Tax BLV , bovine CREB2, or p53 (500 ng).…”
Section: Methodsmentioning
confidence: 99%